Réponses

2012-10-02T19:14:59+02:00

A : -7 x 5 + 18 : 3 - 10 = -35 + 6-10= -45 + 6= -39
B : ( 15 - 6 ) x (3 - 10 ) = 9 x (-7) = -49
C : 9 x 6 - [ 7 - 8 x ( -3 + 5 )] =9x6 - [7-8x2]

                                            = 9x6 - [7-16]

                                            = 9x6 - [-9]

                                            = 9x6 + 9

                                            = 54 + 9= 63

Meilleure réponse !
2012-10-02T19:18:40+02:00

A : (-7*5)+(18/3)-10

= (-35) +6-10

=-39

 

B: (15-6)*(3-10)

=9*(-7)

=-63

 

C:9*6-[7-8*(-3+5)]

= 54-[7-8*2]

= 54-(7-16)

=54-(-9)

=63